Conservative surgery for menorrhagia (Greenwich Medical Media, 2002)
This book is the first to describe all of the currently available methods of treatment of this common condition. Written by some of the world's leading experts in the field, it allows the reader to easily compare instruments and techniques, and provides them with a comprehensive overview of the subject.